Overexpression of Bcl-2 as a proxy redox stimulus to enhance activity of non-viral redox-responsive delivery vectors - Manickam, Devika S (2008)
Redox-sensitive non-viral delivery systems exploit intracellular reducing environment to improve the efficacy of the delivery of nucleic acids by selectively releasing the cargo in the subcellular space. Bcl-2 overexpression is frequently observed in human cancers and is closely associated with increased resistance to chemotherapy and radiotherapy. One of the biochemical alterations accompanying Bcl-2 overexpression is the increase in cellular glutathione (GSH) levels. In this study, we hypothesize that such increase of GSH concentrations will selectively enhance the transfection activity of redox-sensitive delivery systems in cells overexpressing Bcl-2. Transfection studies were conducted in MCF-7 mammary carcinoma cells and MCF-7 clones overexpressing Bcl-2. It was confirmed that Bcl-2 overexpression resulted in the expected increase in GSH concentrations. Redox-sensitive complexes containing plasmid DNA, mRNA, antisense oligodeoxynucleotides, and siRNA exhibited selectively increased activity in cells overexpressing Bcl-2 compared to non-redox complexes. The effect of Bcl-2 overexpression on the selective enhancement of transfection was highly dependent on the type of the delivered nucleic acid, and was most pronounced for mRNA. This study shows that Bcl-2 overexpression can serve as a proxy redox stimulus to enhance the activity of all major classes of potential nucleic acid therapeutics, when delivered using redox-sensitive vectors.